2015
DOI: 10.1007/s40618-015-0283-x
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-modified albumin levels in overt and subclinical hypothyroidism

Abstract: Increase of MDA and IMA levels with decreased antioxidant status indicate the presence of OS in hypothyroid patients, which was more pronounced in OHT patients. Elevated levels of IMA can be a clinically useful marker of protein oxidative damage and OS in hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…Studies suggested that elevated IMA levels can be a clinically useful marker of oxidative damage to protein and OXs in hypothyroidism [19]. However, results of IMA in SCH are inconsistent and inconclusive [20][21][22]. In the present study, LT4 replacement in SCH patients caused a significant decrease in IMA levels.…”
Section: Discussionmentioning
confidence: 44%
“…Studies suggested that elevated IMA levels can be a clinically useful marker of oxidative damage to protein and OXs in hypothyroidism [19]. However, results of IMA in SCH are inconsistent and inconclusive [20][21][22]. In the present study, LT4 replacement in SCH patients caused a significant decrease in IMA levels.…”
Section: Discussionmentioning
confidence: 44%
“…To normalize the effect of albumin levels, the ratio of IMA to albumin (IMAR) was calculated and was found to be significantly increased in these athletes after running than the levels before physical activity (p = 0.000). Increased IMA levels in pre-eclampsia were found to be associated with increased IMAR in other studies carried out in diverse medical conditions [22,23].…”
Section: Discussionmentioning
confidence: 50%
“…Level of IMA in hypothyroidism has been a controversial issue since long. Reddy SV et al 9 have shown increased IMA in both overt and subclinical hypothyroidism and have shown significant positive correlation of IMA with TSH in overt hypothyroidism. In yet another study done by Ma S.G et al, IMA was found to be higher in overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 94%
“…At one end studies have shown increased level of IMA in cases of hypothyroidism, while at the same times studies have shown lower level of IMA. [9][10] There are even studies which have not found any difference in the level of IMA in normal control and hypothyroid subjects . 11 Hence this study was planned to study the level of IMA in newly diagnosed subjects of hypothyroidism who were not on any treatment.…”
Section: Introductionmentioning
confidence: 99%